Distal Fusion Level Selection in Scheuermann's Kyphosis: A Comparison of Lordotic Disc Segment Versus the Sagittal Stable Vertebrae. (May 2017) - Kim, Han Jo; Nemani, Venu; Boachie-Adjei, Oheneba; Cunningham, Matthew E.; Iorio, Justin A.; O'Neill, Kevin; Neuman, Brian J.; Lenke, Lawrence G.
Study Design: Retrospective study. Objective: To compare 2 methods of selecting the lowest instrumented vertebra (LIV) on the rates of revision surgery for distal junctional kyphosis (DJK) following treatment for Scheuermann's kyphosis (SK). Methods: A retrospective review of patients who have undergone surgical treatment for SK was performed. Forty-four patients were divided into 2 groups based on intervention: Group 1 (n = 26) included patients who had an LIV distal to or at the sagittal stable vertebrae (SSV), and Group 2 (n = 18) included patients who had an LIV proximal to the SSV. For each group, demographic, radiographic, and revision surgery data was analyzed. Results: The average follow-up was 3.1 years. There were no differences among demographic variables between the groups. Preoperative and postoperative thoracic kyphosis, lumbar lordosis, and sagittal balance were not different between groups. Postoperatively, Group 1 demonstrated a significantly greater average lordotic disc angle below the LIV compared with Group 2 (Group 1, −6.2 ± 4.3° vs Group 2, −2.9 ± 5.8°; P = .02). In a subgroup analysis, extending fusions to the sagittal stable vertebra rather than the first lordotic disc resulted in fewer distal LIV complications necessitating revision surgery compared with fusing short of the SSV (5% vs 36.3%, P = .04). Conclusion: The SSV method may reduce complications secondary to distal junctional failure, but at the expense of incorporating additional motion segments in a typically young population.